Voice synthesis using power-balanced simulation of a quasi-1D model of the vocal apparatus - Risse, Thomas; Hélie, Thomas; Silva, Fabrice (Frontiers in Signal Processing, 2025)
The vocal apparatus is a biophysical dynamic system capable of self-oscillation, which involves fluid–structure interactions and human control. This study on the sound synthesis of voiced sounds presents a physical quasi-1D model of the vocal apparatus in the port-Hamiltonian framework and its validation through numerical experiments. The modelling ensures balanced power exchanges between fluid, tissues, and human control. Fluid is represented in the larynx and in the vocal tract using a unified 1D PDE handling transverse geometry variations. A regularisation procedure is introduced to mitigate the numerically stiff behaviour of the model observed at channel closure. Vocal folds and vocal tract walls are represented by lumped element models as well as the radiation load at the lips, which consists of a first-order high-pass filter. Spatial discretisation of the fluid model and temporal discretisation of the full system are made using structure-preserving methods to ensure energy consistency (passivity). The second part of this paper focuses on numerical experiments to progressively characterise the model and assess its validity. These experiments begin with frequency response analysis of a static vocal tract under quasi-linear conditions followed by simulations of vowel transitions (diphthongs) under forced excitation. Next, self-oscillation studies are conducted on an isolated larynx where contact parameters are adjusted. Lastly, full simulations of the self-oscillating vocal apparatus with co-articulation, representing a voice synthesizer capable of articulating vowels, are presented. The dynamics are also analysed in terms of energy transfer and passivity. Finally, these results are discussed to establish a basis for future model refinements and to identify directions for enhancing the accuracy and realism of vocal synthesis.